Update of P2Y receptor pharmacology: IUPHAR Review 27. (6th April 2020) - Jacobson, Kenneth A.; Delicado, Esmerilda G.; Gachet, Christian; Kennedy, Charles; von Kügelgen, Ivar; Li, Beibei; Miras‐Portugal, M. Teresa; Novak, Ivana; Schöneberg, Torsten; Perez‐Sen, Raquel; Thor, Doreen; Wu, Beili; et al.
Abstract : Eight G protein‐coupled P2Y receptor subtypes respond to extracellular adenine and uracil mononucleotides and dinucleotides. P2Y receptors belong to the δ group of rhodopsin‐like GPCRs and contain two structurally distinct subfamilies: P2Y1, P2Y2, P2Y4, P2Y6, and P2Y11 (principally Gq protein‐coupled P2Y1 ‐like) and P2Y12–14 (principally Gi protein‐coupled P2Y12 ‐like) receptors. Brain P2Y receptors occur in neurons, glial cells, and vasculature. Endothelial P2Y1, P2Y2, P2Y4, and P2Y6 receptors induce vasodilation, while smooth muscle P2Y2, P2Y4, and P2Y6 receptor activation leads to vasoconstriction. Pancreatic P2Y1 and P2Y6 receptors stimulate while P2Y13 receptors inhibits insulin secretion. Antagonists of P2Y12 receptors, and potentially P2Y1 receptors, are anti‐thrombotic agents, and a P2Y2 /P2Y4 receptor agonist treats dry eye syndrome in Asia. P2Y receptor agonists are generally pro‐inflammatory, and antagonists may eventually treat inflammatory conditions. This article reviews recent developments in P2Y receptor pharmacology (using synthetic agonists and antagonists), structure and biophysical properties (using X‐ray crystallography, mutagenesis and modelling), physiological and pathophysiological roles, and present and potentially future therapeutic targeting. Abstract :